Washington Paper - Velocity of Bodies of Different Specific Gravity Falling in Water. - R. H. Richards; A. E. Woodward (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1890)
In Rittinger's Aufbereitungskunde of 1867 occurs (p. 195) the following table, which shows the rate of falling in water of fragments of minerals, of irregular shapes and of five different specific gravities: Diameter of particles in millimeters. 10 8 6 4 3 2 1 .5 Sp. Or. Velocity in meters per second. Auriferous silver, 16..9 .8 .7 .57 .5 .4 .29 .20 Galena,. ..7.5 .62 .55 .48 .39 54 .28 .20 .14 Pyrites,. ..5.0 .49 .43 .38 .30 .26 .22 .15 .10 Quartz,. ..2.6 -30 .27 24 .19 .17 .14 .10 .07 Coal,. ..1.3 .13 .12 .10 .08 .07 .06 .04 .03 With the purpose of extending this valuable table, to cover a larger number of minerals and sizes of each mineral, and of making it more easy of application in deciding upon a sieve-scale for any group of minerals, we have prepared the curves of velocity of fall of bodies in water shown in Plates I., XI., 111. and IV., using Rittinger's formula V= 2.44d(8 —1) where V= velocity in millimeters per second. " D = diameter of particles in meters. " 8 = specific gravity of the mineral. These curves embrace a large number of specific gravities, and for each specific gravity the relation of the diameter of the mineral particle to the velocity of its fall in water is given for all diameters and velocities used in practice. The second diagram is an enlargement of the lower left-hand corner of the first, the third bears the same relation to the second, and in like manner the fourth to the third. Plate I, therefore, covers the work of the coarsest jigging 2 inches in diameter; and under